KONFLIK PERBATASAN PEMERINTAH DAERAH (Studi Kasus: Perebutan Gunung Kelud Antara Pemerintah Daerah Kabupaten Blitar dengan Kabupaten Kediri) - Sari, Ira Permata (Jurnal Mahasiswa Ilmu Pemerintahan, 2014)
The government district of Blitar and Kediri around 2001-2002 years ago until now (2013) is conflicting to gain Kelud by claim as the legal owner of Kelud. Each of the government district, draw up a budget fund conflict in the budget revenue and public spending for win the conflict. This conflict was facilitated by the East Java government with Decree Issued governor number 188/113/KPTS/013/2012 in date 28 February 2012 about firmness of boundaries which mention that Kelud is include in Kediri District. In fact, Decree Issued governor 188 get some rejection from Blitar District Government. Meanwhile now have been firmness by governor that conflict of Kelud is still in the status quo. This study raised two important points, first, on the border conflict between the local government district of Kediri and Blitar with explanations to obtain the conflict process is still vague. Secondly, about the factors which hinder and support the process of the resolution conflict. Then data was taken by conducting the interview, documentation, and observation, by used purposive sampling, more over the result of this study is analyzed by used Ralf Gustav Dahrendorf Theory Conflict. In the absence of conflict is found the firmness from the home ministry of boundaries between regions in Indonesia, legislators who support the conflict in order to pursue Kelud as its territory without considering other aspects, NGOs in two districts mutually reinforcing movement to defend the interests of the region instead of the interests of the people of both counties, leadership governor is less open and decisive for decided. There is no agreement rules about the employing of border forest in Kelud between forestry service of Blitar and Kediri. Both governments want Kelud as his own, whereas Kelud were among three districts, namely Malang. Moreover, role of local newspapers in this conflict was not as the turbid conflict, but only help to create public opinion for realize the importance. Inhibiting the process of conflict resolution, namely, first, the governor authority functions as a facilitator not openly assertive and, secondly, the extent of autonomy is only understood it just run to get a revenue decentralization and welfare of their own society without understanding the Homeland and understanding of democracy . The third attitude organizers prestige governments retreat from conflict. The arrangement of this conflict can be supported by consolidated between NGOs in both government district, and the movement from the civil society for give voice to their desire without politic element from the government district. Key Words: Conflict, Government, Kelud, Process, Hindering Factors and Supporting